Bicuspid Aortic Valve Outcomes - Rodrigues, I (2017)
BACKGROUND: Bicuspid aortic valve is the most common CHD. Its association with early valvular dysfunction, endocarditis, thoracic aorta dilatation, and aortic dissection is well established. OBJECTIVE: The aim of this study was to assess the incidence and predictors of cardiac events in adults with bicuspid aortic valve. METHODS: We carried out a retrospective analysis of cardiac outcomes in ambulatory adults with bicuspid aortic valve followed-up in a tertiary hospital centre. Outcomes were defined as follows: interventional - intervention on the aortic valve or thoracic aorta; medical - death, aortic dissection, aortic valve endocarditis, congestive heart failure, arrhythmias, or ischaemic heart disease requiring hospital admission; and a composite end point of both. Kaplan-Meier curves were generated to determine event rates, and predictors of cardiac events were determined by multivariate analysis. RESULTS: A total of 227 patients were followed-up over 13±9 years; 29% of patients developed severe aortic valve dysfunction and 12.3% reached ascending thoracic aorta dimensions above 45 mm. At least one cardiac outcome occurred in 38.8% of patients, with an incidence rate at 20 years of follow-up of 47±4%; 33% of patients were submitted to an aortic valve or thoracic aorta intervention. Survival 20 years after diagnosis was 94±2%. Independent predictors of the composite end point were baseline moderate-severe aortic valve dysfunction (hazard ratio, 3.19; 95% confidence interval, 1.35-7.54; p<0.01) and aortic valve leaflets calcification (hazard ratio, 4.72; 95% confidence interval, 1.91-11.64; p<0.005). CONCLUSIONS: In this study of bicuspid aortic valve, the long-term survival was excellent but with occurrence of frequent cardiovascular events. Baseline aortic valve calcification and dysfunction were the only independent predictors of events.